THERMAL ANALYSIS AND PERFORMANCE OF THE PYROLYSIS FUNCTION - Richard Pardomuan Sinaga; I Gede Eka Lesmana (Universitas Muhammadiyah Semarang, 2022)
Biomass-fueled pyrolysis furnace is one approach to utilizing biomass as an alternative fuel and reducing the accumulation of plastic waste, where the furnace works to heat the plastic pyrolysis reactor and the oil cycle heat exchanger simultaneously. Where plastic pyrolysis produces gas to be converted into liquid fuel, and the heat in the oil cycle is used as a reference for the ORC (organic Rankine cycle) heat source in future research. Because the furnace has just been manufactured and no experimental analysis has been carried out regarding the testing method for the output product, therefore the purpose of this study is to analyze the effect of the fuel use method on the volume, quality, and efficiency of pyrolysis oil, maximum oil cycle temperature, and furnace performance. In this study, the type of plastic used is PET (polyethylene terephthalate) from used mineral water bottles that have been chopped with an initial mass of 5.2 kg and poured into a 26 kg reactor which is expected to reach pyrolysis gas at a temperature of 335°C which is then cooled by fixed bed condenser with a cooling rate of 19 liters/minute. Meanwhile, in the oil cycle using SAE 20W-50 engine oil at 1.3 liters/minute, it is expected to reach oil at a temperature above 90°C. The test was carried out twice based on the method of using the fuel, where in the first experiment using coconut shell charcoal briquettes as the main fuel with a feed of 5.0 kg/hour and LPG as a burner every 20 minutes per briquette feed, while the fuel in the second experiment only use LPG. The first pyrolysis experiment obtained 645 ml of pyrolysis oil with a density of 797-869 kg/m3 and a pyrolysis efficiency of 16.125%, while the second experiment obtained 986 ml with a density of 894-928 kg/m3 and a pyrolysis efficiency of 24.65%. The maximum temperature reached by the oil cycle was 122°C in the first experiment and 95°C in the second experiment. And the performance of the furnace in the first experiment showed that the thermal efficiency of the furnace was 38.84% and 76.59% in the second experiment.